Pemodelan De Novo Programming dengan Metode Simpleks dan Metode Cutting Plane Untuk Mengoptimalkan Perencanaan Produksi Usaha Kecil Menengah - Safitri, Nurul; Kiftiah, Mariatul; Pasaribu, Meliana (Universitas Negeri Gorontalo, 2024)
Small and Medium Enterprises (SMEs) Aneka Jamu Traditional is a small and medium-sized enterprise in the field of herbal medicine production. The SME produces 3 types of traditional herbal medicine, namely angin herbal medicine, urat herbal medicine, and peluntur herbal medicine. In producing herbal medicine, the number of products produced does not match the availability of raw materials available so that the production costs incurred will certainly affect profits. This is due to improper production planning. The purpose of this research is to determine the right production planning in order to obtain maximum profit. One of the developments of linear programming models that specifies budget constraints is the de novo programming model. The de novo programming model can provide a combination of the best number of product to be produced nd the proposed use of resources based on the available budget. The de novo programming model is used to form a raw material or budget constraint problem into a mathematical model. Furthermore, it is solved using the simplex method. In this research, the optimal solution required is an integer so the calculation is continued with the cutting pane method. The profit earned by Aneka Jamu Tradisional SMEs amounted of Rp10.473.500/month. Based on the research results, the completion of the de novo programming model with simplex method and cutting plane method obtained x_1=3.000, x_2=3,000, x_3=1,657 with Z = 12,386,733. This means that to obtain optimal profits, SMEs must produce 3.000 packs of angin herbs, 3.000 packs of urat herbs, and 1.657 packs of peluntur herbs with a profit of Rp12,386,733/month.